Design of substitution nodes (S-Boxes) of a block cipher intended for preliminary encryption of confidential information - Ardabek Khompysh; Nursulu Kapalova; Kunbolat Algazy; Dilmukhanbet Dyusenbayev; Kairat Sakan (Cogent Engineering, 2022)
This paper considers a new method for obtaining an S-box, which is one of the nonlinear transformations used in modern block-symmetric cipher systems. This method is based on modular arithmetic, that is, exponentiation modulo polynomial in extended Galois fields [Formula: see text]. The indicators and criteria of efficiency of the obtained S-box (balance, Hamming distance, distribution criteria, autocorrelation, algebraic immunity, cyclic structure of the S-box) are analyzed. The cryptographic characteristics are presented in comparison with the substitution boxes of known modern block ciphers. In addition, the resulting S-box was investigated by the methods of linear and differential cryptanalysis. In the future, the proposed S-box will be used in the developed encryption algorithm designed for the pre-encryption of confidential information.